Formulation and development of transdermal drug delivery system of antifertility drugs using combination of polymers - SHIKHABAGHEL CHAUHAN; TANVEERNAVED (International Journal of Pharma and Bio Sciences, 2017)
The rising population of India is a cause of concern today. High population is a hurdle for nation development and growth. Although a large number of Contraceptives are available nowadays, but even today, there are concerns associated with them. Oral contraceptives have been widely linked with the cause of venous thrombosis and pulmonary emboli in women. Therefore, it was decided to investigate formulation and development of transdermal patch containing Ethinylestradiol (EE) and Medroxy progesterone acetate (MPA). The combination therapy of Ethinylestradiol (EE) and Medroxyprogesterone acetate (MPA) transdermal patch has shown efficacy in antifertility treatment. The present studies were designed to develop a suitable matrix type Transdermal Drug delivery system (TDDS) of EE and MPA using various polymers combinations. Nine formulations (F1-F9) were developed by varying the concentration of polymers HPMC, Ethylcellulose and Polyvinylpyrrolidone (PVP) and keeping the drug load constant. Propylene glycol (PG) was used as penetration enhancer. Physical parameters and drug excipient interaction studies were evaluated in all the formulations were simultaneously characterized in a thermostatically controlled modified Franz Diffusion cell. Based on physical parameters and in vitro skin permeation profile formulation F8 was found to be the best and chosen as final patch formulation for further studies. Stability profile of formulation F8 depicted stability up to 3 months.The Antifertility patch shows future potential for the further research and need of conduction of human cinical trials for further investigations.